The effect of ambient temperature on infrared thermographic images of joints in the distal forelimbs of healthy racehorses. (May 2017) - Soroko, Maria; Howell, Kevin; Dudek, Krzysztof
Abstract: The aim of the study was to describe the dependence on ambient temperature of distal joint temperature at the forelimbs of racehorses. The study also investigated the influence of differing ambient temperatures on the temperature difference between joints: this was measured ipsilaterally (i.e. between the carpal and fetlock joints along each forelimb) and contralaterally (i.e. between the same joints of the left and right forelimbs). Sixty-four healthy racehorses were monitored over 10 months. At each session, three thermographic images were taken of the dorsal, lateral and medial aspects of the distal forelimbs. Temperature measurements were made from regions of interest (ROIs) covering the carpal and fetlock joints. There was a strong correlation between ambient temperature and absolute joint temperature at all ROIs. The study also observed a moderate correlation between ambient temperature and the ipsilateral temperature differences between joints when measured from the medial and lateral aspects. No significant correlation was noted when measured dorsally. The mean contralateral temperature differences between joints were all close to 0 °C. The data support previous reports that the temperature distribution between the forelimbs of the healthy equine is generally symmetric, although some horses differ markedly from the average findings. Highlights: Ambient temperature and absolute joint temperature were correlated in racehorses. Within-limb temperature gradients also correlated with ambient temperature. Typical temperature distribution between forelimbs in healthy horses was symmetric. A few horses exhibited asymmetric temperature distribution across the forelimbs.